Otolith Chemistry Reveals Natal Region of Larval Capelin in Coastal Newfoundland, Canada - Tripp, Ashley; Murphy, Hannah M.; Davoren, Gail K. (Frontiers in Marine Science, 2020)
Identifying natal origins of animals is key to determining the relative productivity of natal habitats, dispersal of individuals among local populations (i.e., connectivity), and, ultimately, metapopulation dynamics. As marine fish larvae have a high potential for dispersal, natural tags such as otolith chemistry are often used to determine natal origins. Trace elements may be incorporated into embryonic otoliths while larvae are developing in the egg, resulting in chemical signatures in the pre-hatch region of the otolith that reflect the natal habitat. Our goal was to determine whether the natal origins of 1- to 3-day-old larval capelin (Mallotus villosus), a key forage fish in many northern marine ecosystems, could be determined using otolith chemistry. We sampled larvae from five Newfoundland regions (i.e., embayments: Placentia Bay, St. Mary’s Bay, Witless Bay, Trinity Bay, and Notre Dame Bay) during July–August 2019 to quantify regional differences in otolith chemistry. Additionally, eggs/larvae were field-reared within two regions over multiple years (Notre Dame Bay: 2014, 2015, 2018, and 2019; Trinity Bay: 2018 and 2019) to quantify interannual variation in region-specific otolith chemistry. Multielemental otolith signatures (i.e., Mg, Mn, Zn, Sr, and Ba), as determined by laser ablation inductively coupled plasma–mass spectrometry (LA ICP–MS), differed significantly among regions, with individuals classified into their natal region with 78% success (region-specific success: 68–100%). Classification success into natal region remained high (67–76%) despite interannual variation in otolith trace element concentrations within regions. Characterizing region-specific otolith chemical signatures that reflect natal origins of capelin larvae is the first step in determining the productivity and relative contributions of different regions of coastal Newfoundland to capelin recruitment.